PERANAN KOMISI PEMBERANTASAN KORUPSI (KPK) SEBAGAI LEMBAGA ANTI KORUPSI DI INDONESIA - Achmad Badjuri (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
The removal of corruption is one of the important agenda of government in the attempt ofstate implementation, which is clean and free from corruption, collution, and nepotism. Theremoval of corruption is also a national and international agenda. The international institution isalso determined about joined commitment to fight the corruption. One of the obstacles in thedeveloping country to achieve prosperity is because of the excessive corruption practice, bothinvolving the public sector official and broader community. Corruption is a crime with extraordinary effect on the life of national economic. The corruption money is the lost potential of stateincome and become the illegal source of income of its doer. The corruption money is supposedlythe government money to fund the pro society governmental programs, such as the removal ofpoverty, education for the poor children, the improvement of the quality of public health service,capital assistance for the small scale entrepreneur, etc. The actor of corruption had arrogated theright of poor people whose supposedly helped and improved by the government. The Committee ofCorruption Removal (KPK) as the anti corruption agency in Indonesia hopefully become the mosteffective and efficient corruption removal agency.Key Words: corruption, collution, nepotism, systematic crime, state financial loss, the committeeof corruption removal